MARKET ECONOMY AND LANGUAGE: THE IMPACT OF ECONOMIC REFORMS ON THE UZBEKISTAN LANGUAGE (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
In this article, we analyzed the impact of the transition to a market economy in Uzbekistan on the Uzbek language. New concepts and terms that emerged as a result of economic reforms and the processes of their expression in the Uzbek language were studied. The article reveals the intersection of linguistics and economics, substantiates the need to modernize the state language through the linguistic interpretation of economic reforms.